(untitled) (Kronika Bydgoska, 2013)
In 1920, under the decisions of the Treaty of Versailles, Bydgoszcz returned to the motherland. Along with the regions of Kuyavia and Pomerania, the city was taken over by the troops of general Józef Haller. At the head of his army, the general moved into the city. He became a symbol of the establishment of Polish power, gaining general liking of the residents. Under his command, Bydgoszcz residents fought in the ranks of the ”Blue Army”, and later in the Polish-Bolshevik war in 1920. In the inter-war period, the tradition of fame and memory of the "Blue General" was cultivated vy the Pomeranian Council of the Association of General Haller's Soldiers, which was seated in Bydgoszcz. During World War Two, a part of his soldiers participated in the fight for Poland's freedeom. After the war, general Haller shared the emigrant's fate and stayed in London till the end of his life. When the communists had taken power in Poland, it was impossible to cultivate the memory of the merits of the "emigration" general. Revival of the operation of patriotic organisations, including the Association of General Haller's Soldiers, was forbidden. The democratic transformations in Poland after the year 1989 allowed operation of different associations and communities, Haller organistations as well. In 2000, the Polish General Haller and His Soldiers Memorial Association was established in Jurczyce, the birthplace of general Józef Haller. Bydgoszcz residents also participated in the establishment of this association. One of the branches of the General Józef Haller and His Soldiers Memorial Association was established in Bydgoszcz. The main goal of this association was propagation of the fame and memory of general Józef Haller and his soldiers amidst Bydgoszcz residents, especially school youth. The associaion took many educational-patriotic documentation initiatives. It was active in the years 2000-2013.